Access to Public Sector Information Volume 2 Law, Technology and Policy - Fitzgerald, Brian (Sydney University Press, 2010)
On the back of the growing capacity of networked digital information technologies to process and visualise large amounts of information in a timely, efficient and user-driven manner, we have seen an increasing demand for better access to and re-use of public sector information. The story is not a new one. Share knowledge and together we can do great things; limit access and we reduce the potential for opportunity. The two volumes of this book seek to explain and analyse the global shift in the way we manage public sector information. In doing so they collect and present papers, reports and submissions on the topic by the leading authors and institutions from across the world. These provide people tasked with mapping out and implementing information policy with reference material and practical guidance. Volume 2 presents a selection of the key reports and submissions that have been published over the last few years. The volumes are sold separately and as a set.